Blogs as Predictors of Movie Success - Sadikov, Eldar; Parameswaran, Aditya; Venetis, Petros (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Analysis of a comprehensive set of features extracted from blogs for prediction of movie sales is presented. We use correlation, clustering and time-series analysis to study which features are best predictors.